PERANCANGAN PROMOSI PRIVATE LAUNDRY MELALUI MEDIA BROSUR - IKHSANUL ANWAR, Drs. Ariusmedi, M.Sn, Yofita Sandra, S.Pd, M.Pd (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The purpose of this final work are : (1) to design a media campaign that the system of private laundry customer service offered is better known and understood by the public. Moreover, the customer service system offered a private laundry is still new and is the only laundry that use such a system in the city of Padang (2) designing a media campaign that is more attractive to gain communicative, so that the message and purpose conveyed easy to understand and attract more target audience in order to engage the services of private laundry. The data about media in the promotion can be collected by using observation and interview. Result of final work is a brochures as the primary media that includes all information about private laundry, especially regarding customer service system that is in use. Keywords: private laundry, promotions, customer service, brochure